Adhesive composition for polarizing film, polarizing film, optical film, and image display device

The adhesive composition with a cation scavenger addresses the issue of bright spots in polarizing films by capturing metal components, ensuring superior appearance characteristics even after humidification tests.

JP7617731B2Active Publication Date: 2025-01-20NITTO DENKO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020201976
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-04
Publication Date
2025-01-20
Estimated Expiration
2040-12-04

AI Technical Summary

Technical Problem

Polarizing films used in automotive applications suffer from the occurrence of bright spots due to foreign substances after humidification durability tests, which affect their appearance characteristics.

Method used

An adhesive composition for polarizing films containing a cation scavenger with a coordination site capable of coordinating with metal components, such as zinc, and a reactive group, which captures and incorporates metal components into the polymer structure, preventing the formation of oxalate and bright spots.

Benefits of technology

The adhesive composition significantly suppresses the occurrence of bright spots in polarizing films after humidification durability tests, maintaining excellent appearance characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617731000004
    Figure 0007617731000004
  • Figure 0007617731000005
    Figure 0007617731000005
  • Figure 0007617731000001
    Figure 0007617731000001
Patent Text Reader

Abstract

To provide an adhesive composition for polarizing films that serves as the raw material for the polarizing film having a good appearance with few bright spots caused by foreign matter even after a humidification durability test.SOLUTION: The present invention discloses an adhesive composition for polarizing films that has a cation trapping agent having a coordination portion capable of coordinating with a metal component at two or more sites and a reactive group. There is also disclosed a polarizing film having a polarizer, and an adhesive layer adjacent to the polarizer or an optical film other than the polarizer, wherein the adhesive layer is a cured layer of the adhesive composition for polarizing films. Suitably, the polarizer contains a metal component that can be a divalent metal cation underwater.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition for polarizing films, and further to a polarizing film comprising a polarizer and an adhesive layer adjacent to the polarizer or an optical film other than a polarizer. The polarizing film can be used alone or as an optical film laminated therewith to form image displays such as mobile phones, car navigation devices, personal computer monitors, and televisions. [Background technology]

[0002] Liquid crystal display devices are rapidly expanding into the market for mobile phones, car navigation devices, computer monitors, televisions, etc. Liquid crystal display devices visualize the polarization state by switching liquid crystals, and polarizers are used due to their display principle. In particular, for applications such as TVs, higher brightness, higher contrast, and wider viewing angles are required, and polarizing films are also required to have higher transmittance, higher polarization degree, and better color reproducibility.

[0003] As a polarizer, since it has high transmittance and high polarization degree, for example, an iodine-based polarizer having a structure in which iodine is adsorbed to polyvinyl alcohol (hereinafter also simply referred to as "PVA") and stretched is most commonly used. In general, a polarizing film is used in which transparent protective films are bonded to both sides of a polarizer using a so-called water-based adhesive in which a polyvinyl alcohol-based material is dissolved in water (Patent Document 1 below). As the transparent protective film, triacetyl cellulose, which has high moisture permeability, is used. When the water-based adhesive is used (so-called wet lamination), a drying process is required after bonding the polarizer and the transparent protective film.

[0004] On the other hand, instead of the water-based adhesive, an active energy ray curable adhesive has been proposed. When a polarizing film is produced using an active energy ray curable adhesive, a drying process is not required, so the productivity of the polarizing film can be improved. For example, a radical polymerization type active energy ray curable adhesive using an N-substituted amide monomer as a curable component has been proposed (Patent Document 2 below). The adhesive layer formed using the active energy ray curable adhesive described in Patent Document 2 can fully pass a water resistance test that evaluates the presence or absence of color loss and peeling after immersion in 60°C hot water for 6 hours. However, in recent years, polarizing films are often used not only for mobile applications such as mobile phones, but also for image display devices for in-vehicle applications, and in-vehicle applications need to satisfy durability tests under higher temperature and humidity conditions than mobile applications. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2001-296427 A [Patent Document 2] JP 2012-052000 A Summary of the Invention [Problem to be solved by the invention]

[0006] One durability test required for polarizing films used in vehicle applications is, for example, a humidity durability test in which the film is exposed to an environment of 65°C and 95% humidity for 1000 hours. Here, the present inventors conducted a detailed study on the appearance of the polarizing film after the humidity durability test and found that bright spots due to white hazy foreign matter were generated, particularly at the ends of the polarizing film, resulting in a defective product in terms of appearance characteristics. This phenomenon was observed for the first time after a durability test under a high-temperature and high-humidity environment, and it was necessary to conduct a thorough study to solve the problem.

[0007] The present invention has been developed in view of the above-mentioned circumstances, and has an object to provide an adhesive composition for polarizing films, which can be used as a raw material for polarizing films that suppress the occurrence of bright spots due to foreign matter even after a humid durability test and have excellent appearance characteristics.

[0008] It is a further object of the present invention to provide a polarizing film which suppresses the occurrence of bright spots due to foreign matter even after a humid durability test and has excellent appearance characteristics. [Means for solving the problem]

[0009] The above problems can be solved by the following configuration. That is, the present invention provides a cation having a coordination site capable of being coordinated with a metal component at two or more dentates and a reactive group. capture The present invention relates to an adhesive composition for polarizing films, which comprises an agent.

[0010] In the above adhesive composition for polarized films, the reactive group is preferably at least one type of reactive group selected from the group consisting of a vinyl group, a (meth)acrylic group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a mercapto group, and an alkoxy group.

[0011] In the above adhesive composition for polarizing films, capture The coordination site of the agent has at least two nitrogen atoms, or the cation capture The coordination site of the agent has at least two oxygen atoms, and the cation capture Preferably, the coordination site of the agent has at least one nitrogen atom and at least one oxygen atom.

[0012] In the above adhesive composition for polarized films, the cation scavenger is preferably at least one selected from the group consisting of aminoalkylacrylamides, aminoalkylacrylates, and reaction products of acetoacetyl- or acetoacetoxyl-containing compounds with primary amine compounds.

[0013] The adhesive composition for polarized films preferably further contains an active energy ray-curable component.

[0014] In the above adhesive composition for polarizing films, when the total amount of the adhesive composition for polarizing films is taken as 100% by weight, capture The content of the agent is preferably 0.5 to 15% by weight.

[0015] The present invention also relates to a polarizing film comprising a polarizer and an adhesive layer adjacent to the polarizer or an optical film other than the polarizer, wherein the adhesive layer is a cured layer of any of the adhesive compositions for polarizing films described above.

[0016] In the above polarizing film, the polarizer preferably contains a metal component capable of becoming a divalent metal cation in water.

[0017] In the polarizing film, the metal component is preferably zinc.

[0018] In the above polarizing film, it is preferable that the polarizing film comprises a polarizer and an optical film laminated on at least one surface of the polarizer via an aqueous adhesive layer, and the adhesive layer is provided on the surface of the optical film opposite the aqueous adhesive layer.

[0019] The present invention further relates to an optical film comprising at least one laminate of any of the polarizing films described above, and an image display device comprising any of the polarizing films described above and / or any of the optical films described above. Effect of the Invention

[0020] Polarizing films used for in-vehicle applications and the like are required to have excellent appearance characteristics even after a humid durability test in which the film is exposed to an environment of 65°C and 95% humidity for 1000 hours. In a polarizing film having an adhesive layer formed using the adhesive composition for polarizing films according to the present invention as a raw material, the adhesive composition for polarizing films contains a cation having a coordination site capable of being coordinated to a metal component with two or more sites and a reactive group. capture Therefore, after the humid durability test, the occurrence of bright spots due to foreign matter in the polarizing film can be significantly suppressed, resulting in excellent appearance characteristics of the polarizing film.

[0021] In particular, even when a polarizing film having an adhesive layer formed using the adhesive composition for polarizing films according to the present invention as a raw material includes a polarizer containing a metal component that can become a divalent metal cation in water, particularly zinc, the polarizing film has excellent appearance characteristics. The reason why this effect is obtained is not clear, but the following reasons can be assumed, for example.

[0022] In a polarizing film having a polarizer and an adhesive layer adjacent to the polarizer or an optical film other than the polarizer, during a humidity durability test, metal components contained in the polarizer that can become divalent metal cations in water, particularly zinc, move into the adhesive layer at the end of the polarizing film via steam or condensation. Here, components other than those contained in the raw adhesive composition, such as oxalic acid, exist in an ionized state in the adhesive layer, but unless they combine with a metal component to become an oxalate, the oxalic acid is not detected as a foreign substance in the adhesive layer. However, during a humidity durability test, if a specific metal component contained in the polarizer is mixed into the adhesive layer from the end, the ionized oxalic acid and the metal component combine to generate an oxalate, particularly at the end of the adhesive layer, which is detected as a foreign substance as a white bright spot. As a result, the appearance characteristics of the polarizing film are deteriorated.

[0023] In a polarizing film in which an adhesive layer is formed using the adhesive composition for polarizing films according to the present invention as a raw material, even if a specific metal component contained in a polarizer is mixed into the adhesive layer from the edge, cationic captureThe agent contains metal components. capture In particular, in the present invention, since the cation scavenger has a coordination site capable of coordinating with at least two or more metal components, the cation scavenger binds the metal component prior to the binding of oxalic acid to the metal component. capture It should be noted that since the cation scavenger has a reactive group in addition to a coordination site, it is incorporated into the polymer constituting the adhesive when the adhesive composition for polarizing films is cured to form an adhesive layer. Therefore, the captured metal component is also incorporated into the polymer constituting the adhesive layer, so that the bonding between the ionized oxalic acid and the metal component, and further the migration of the oxalate from the edge of the polarizing film to the inside, are suppressed. As a result, the appearance characteristics of the polarizing film are particularly improved even after a humidity durability test.

[0024] The polarizing film according to the present invention has excellent appearance characteristics even after a humid durability test. Even when the polarizer of the polarizing film according to the present invention contains a metal component that can become a divalent metal cation in water, particularly when the metal component is zinc, the adhesive composition for polarizing films, which is a raw material for the adhesive layer, contains a specific cation scavenger, so that the bonding between ionized oxalic acid and the metal component, and further the migration of oxalate from the edge of the polarizing film to the inside, are suppressed. As a result, the appearance characteristics of the polarizing film are particularly improved even after a humid durability test. [Brief description of the drawings]

[0025] [Figure 1] 1 is an example of a schematic cross-sectional view of a polarizing film according to one embodiment of the present invention. [Diagram 2] 4 is a schematic cross-sectional view of another example of a polarizing film according to one embodiment of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] FIG. 1 shows an example of a schematic cross-sectional view of a polarizing film according to an embodiment of the present invention. A polarizing film 10 in this embodiment includes a polarizer 1 and an adhesive layer 5 adjacent to a first optical film 4 other than the polarizer 1. More specifically, a polarizer 1, a first optical film (retardation film) 4 laminated on at least one surface of the polarizer 1 via a water-based adhesive layer 2, and an adhesive layer 5 on the surface of the first optical film 4 opposite to the water-based adhesive layer 2. In particular, the polarizing film 10 in this embodiment includes a second optical film (transparent protective film) 3 laminated on one surface of the polarizer 1 via a water-based adhesive layer 2, a first optical film (retardation film) 4 laminated on the other surface of the polarizer 1 via a water-based adhesive layer 2, an adhesive layer 5 laminated on the first optical film (retardation film) 4, and a third optical film (retardation film) 6 laminated on the adhesive layer 5. The polarizing film 10 further includes an adhesive layer 7 laminated on the third optical film 6, and is laminated on an image display cell or the like via the adhesive layer 7.

[0027] 2 shows another example of a schematic cross-sectional view of a polarizing film according to one embodiment of the present invention. A polarizing film 10 in this embodiment includes a polarizer 1 and an adhesive layer 5 adjacent to the polarizer 1. More specifically, in the polarizing film 10 of this embodiment, a second optical film (transparent protective film) 3 is laminated on one surface of the polarizer 1 via a water-based adhesive layer 2, and a first optical film (retardation film) 4 is laminated on the other surface of the polarizer 1 via an adhesive layer 5. In the polarizing film 10, an adhesive layer 7 is further laminated on the optical film 4, and the polarizing film 10 is laminated on an image display cell or the like via the adhesive layer 7.

[0028] 1 and 2, the aqueous adhesive layer 2 is preferably an aqueous solution (e.g., solids concentration 0.5 to 60% by weight) of an aqueous adhesive such as an isocyanate adhesive, a polyvinyl alcohol adhesive, a gelatin adhesive, a vinyl latex adhesive, or an aqueous polyester adhesive. The thickness of the aqueous adhesive layer 2 is not particularly limited, but is usually about 0.01 μm to 0.5 μm after drying.

[0029] In the polarizing film 10 shown in FIG. 1 and FIG. 2, during the humidity durability test, metal components, particularly zinc, contained in the polarizer 1 and capable of becoming divalent metal cations in water migrate into the adhesive layer 5 via steam or condensation at the end of the polarizing film 10. Here, in the adhesive layer 5, components other than those contained in the raw adhesive composition, such as oxalic acid, are present in an ionized state, but unless they are combined with a metal component to form an oxalate, the oxalic acid is not detected as a foreign substance in the adhesive layer. Here, when a specific metal component contained in the polarizer 10 is mixed into the adhesive layer 5 during the humidity durability test, the ionized oxalic acid combines with the metal component to generate an oxalate, which is detected as a foreign substance in the form of a white bright spot, but in the polarizing film 10 shown in FIG. 1 and FIG. 2, the generation of bright spots due to foreign substances in the adhesive layer is significantly suppressed.

[0030] In the present invention, the polarizing film includes a polarizer and an adhesive layer adjacent to the polarizer or an optical film other than the polarizer. The polarizing film 10 shown in Fig. 1 includes an adhesive layer 5 adjacent to an optical film (retardation film) 4 other than the polarizer 1. The polarizing film 10 shown in Fig. 2 includes an adhesive layer 5 adjacent to the polarizer 1. The adhesive composition for polarizing films according to the present invention, which is a raw material for the adhesive layer, will be described below.

[0031] <Adhesive layer> The adhesive layer is formed by a layer of a cured product of the adhesive composition for polarizing film according to the present invention. The adhesive composition for polarizing film according to the present invention is preferably an active energy ray curable adhesive composition, particularly an electron beam curable, ultraviolet ray curable, or visible light curable adhesive composition. The thickness of the adhesive layer after drying is preferably 0.1 μm to 5.0 μm, more preferably 0.5 μm to 3.0 μm, from the viewpoint of achieving both improved appearance characteristics and adhesive strength of the polarizing film. The active energy ray curable adhesive composition contains an active energy ray curable component, and examples of the active energy ray curable component include a radical polymerizable adhesive composition containing a radical polymerizable compound and a cationic polymerizable adhesive composition containing a cationic polymerizable compound. In the present invention, active energy rays in the wavelength range of 10 nm to less than 380 nm are referred to as ultraviolet rays, and active energy rays in the wavelength range of 380 nm to 800 nm are referred to as visible light.

[0032] The adhesive composition for polarizing films according to the present invention comprises a cation having a coordination site capable of being coordinated to a metal component at two or more dentates and a reactive group. capture Contains the agent.

[0033] The reactive group of the cation scavenger is necessary for reacting with a radical polymerizable compound or a cation polymerizable compound and incorporating the cation scavenger into the polymer constituting the adhesive layer. The reactive group is preferably at least one type of reactive group selected from the group consisting of a vinyl group, a (meth)acrylic group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, and a mercapto group.

[0034] The coordination site of the cation scavenger is a structure capable of being coordinated to a metal component at two or more dentates, such as a structure (i) having at least two nitrogen atoms, a structure (ii) having at least two oxygen atoms, or a structure (iii) having at least one nitrogen atom and at least one oxygen atom.

[0035] Examples of the cation scavenger having the structure (i) include compounds having two or more nitrogen atoms in the molecule and having a reactive group such as an acrylic group, such as aminoalkylacrylamides such as dimethylaminopropylacrylamide, and reaction products of acetoacetyl or acetoacetoxyl group-containing compounds with primary amine compounds, such as a reaction product of 2-acetoacetoxyethyl methacrylate with ethylenediamine.

[0036] Examples of the cation scavenger having the structure (ii) include compounds having two or more oxygen atoms in the molecule and having a reactive group such as an alkoxy group, such as 3-trimethoxysilylpropylsuccinic anhydride.

[0037] Examples of cation scavengers having the structure (iii) include compounds having one or more nitrogen atoms and one or more oxygen atoms in the molecule, and having a reactive group such as an acrylic group, such as aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate.

[0038] From the viewpoint of improving the appearance of the polarizing film, when the total amount of the adhesive composition for polarizing film is taken as 100% by weight, a cationic capture The content of the agent is preferably 0.5 to 15% by weight, and more preferably 1 to 10% by weight.

[0039] The monomer components constituting the radically polymerizable adhesive composition include radically polymerizable compounds. The radically polymerizable compounds include compounds having a radically polymerizable functional group of a carbon-carbon double bond, such as a (meth)acryloyl group or a vinyl group. These monomer components can be either monofunctional radically polymerizable compounds or polyfunctional radically polymerizable compounds having two or more polymerizable functional groups. These radically polymerizable compounds can be used alone or in combination of two or more. As these radically polymerizable compounds, for example, compounds having a (meth)acryloyl group are suitable. In the present invention, (meth)acryloyl means an acryloyl group and / or a methacryloyl group, and "(meth)" has the same meaning hereinafter.

[0040] Examples of the monofunctional radical polymerizable compound include (meth)acrylamide derivatives having a (meth)acrylamide group. (Meth)acrylamide derivatives are preferred in terms of ensuring adhesion to polarizers and various transparent protective films, and in terms of high polymerization rate and excellent productivity. Specific examples of the (meth)acrylamide derivative include N-alkyl group-containing (meth)acrylamide derivatives such as N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hexyl(meth)acrylamide; N-hydroxyalkyl group-containing (meth)acrylamide derivatives such as N-methylol(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and N-methylol-N-propane(meth)acrylamide; N-aminoalkyl group-containing (meth)acrylamide derivatives such as aminomethyl(meth)acrylamide and aminoethyl(meth)acrylamide; N-alkoxy group-containing (meth)acrylamide derivatives such as N-methoxymethylacrylamide and N-ethoxymethylacrylamide; and N-mercaptoalkyl group-containing (meth)acrylamide derivatives such as mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide. Examples of heterocycle-containing (meth)acrylamide derivatives in which the nitrogen atom of the (meth)acrylamide group forms a heterocycle include N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.

[0041] Among the (meth)acrylamide derivatives, from the viewpoint of adhesion to polarizers and various transparent protective films, N-hydroxyalkyl group-containing (meth)acrylamide derivatives are preferred, and examples of the monofunctional radical polymerizable compound include various (meth)acrylic acid derivatives having a (meth)acryloyloxy group. Specific examples of the acrylate include (meth)acrylic acid (carbon number: 1 to 20) alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate.

[0042] Examples of the (meth)acrylic acid derivatives include cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, and the like. Polycyclic (meth)acrylates such as diethyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc.; alkoxy group- or phenoxy group-containing (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, alkylphenoxypolyethylene glycol (meth)acrylate, etc.; and the like.

[0043] Examples of the (meth)acrylic acid derivatives include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. (meth)acrylate, hydroxyl group-containing (meth)acrylates such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanedimethanol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate; epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate glycidyl ether; 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, and 2,2,2-trifluoroethylethyl (meth)acrylate; Acrylates, halogen-containing (meth)acrylates such as tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; alkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; 3-oxetanylmethyl (meth)acrylate, 3-methyl-oxetanylmethyl (meth)acrylate; acrylate, 3-ethyl-oxetanylmethyl (meth)acrylate, 3-butyl-oxetanylmethyl (meth)acrylate, 3-hexyl-oxetanylmethyl (meth)acrylate and other oxetane group-containing (meth)acrylates; tetrahydrofurfuryl (meth)acrylate, butyrolactone (meth)acrylate and other (meth)acrylates having a heterocycle; hydroxypivalic acid neopentyl glycol (meth)acrylic acid adduct; and p-phenylphenol (meth)acrylate.

[0044] Furthermore, examples of the monofunctional radically polymerizable compound include carboxyl group-containing monomers such as (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0045] Examples of the monofunctional radically polymerizable compound include lactam-based vinyl monomers such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, and methylvinylpyrrolidone; and vinyl monomers having a nitrogen-containing heterocycle such as vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, and vinylmorpholine.

[0046] In addition, as the monofunctional radical polymerizable compound, a radical polymerizable compound having an active methylene group can be used. The radical polymerizable compound having an active methylene group is a compound having an active double bond group such as a (meth)acrylic group at the end or in the molecule, and having an active methylene group. Examples of the active methylene group include an acetoacetyl group, an alkoxymalonyl group, and a cyanoacetyl group. It is preferable that the active methylene group is an acetoacetyl group. Specific examples of radical polymerizable compounds having an active methylene group include acetoacetoxyalkyl (meth)acrylates such as 2-acetoacetoxyethyl (meth)acrylate, 2-acetoacetoxypropyl (meth)acrylate, and 2-acetoacetoxy-1-methylethyl (meth)acrylate; 2-ethoxymalonyloxyethyl (meth)acrylate, 2-cyanoacetoxyethyl (meth)acrylate, N-(2-cyanoacetoxyethyl)acrylamide, N-(2-propionylacetoxybutyl)acrylamide, N-(4-acetoacetoxymethylbenzyl)acrylamide, and N-(2-acetoacetylaminoethyl)acrylamide. The radical polymerizable compound having an active methylene group is preferably an acetoacetoxyalkyl (meth)acrylate.

[0047] Examples of polyfunctional radically polymerizable compounds having two or more polymerizable functional groups include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropanediol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentylglycol diglycidyl ether ... Examples of the ester compound include esters of (meth)acrylic acid and polyhydric alcohols such as diol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, dioxane glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerin tetra(meth)acrylate; and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene. Specific examples include Aronix M-220 (manufactured by Toagosei Co., Ltd.), Light Acrylate 1,9ND-A (manufactured by Kyoeisha Chemical Co., Ltd.), Light Acrylate DGE-4A (manufactured by Kyoeisha Chemical Co., Ltd.), Light Acrylate DCP-A (manufactured by Kyoeisha Chemical Co., Ltd.), SR-531 (manufactured by Sartomer Co., Ltd.), CD-536 (manufactured by Sartomer Co., Ltd.), etc. In addition, various epoxy (meth)acrylates, urethane (meth)acrylates, polyester (meth)acrylates, various (meth)acrylate-based monomers, etc. may be mentioned as necessary.

[0048] The adhesive composition for polarizing films according to the present invention may contain an acrylic oligomer obtained by polymerizing a (meth)acrylic monomer in addition to the radically polymerizable compound. By containing an acrylic oligomer in the adhesive composition, it is possible to reduce the cure shrinkage when the composition is irradiated with active energy rays and cured, and to reduce the interfacial stress between the adhesive layer and the adherend, such as a polarizer or an optical film. As a result, it is possible to suppress a decrease in the adhesion between the adhesive layer and the adherend.

[0049] In consideration of workability and uniformity during application, it is preferable that the adhesive composition for polarizing films has a low viscosity, and therefore it is preferable that the acrylic oligomer obtained by polymerizing the (meth)acrylic monomer also has a low viscosity. As an acrylic oligomer having a low viscosity and capable of preventing the curing shrinkage of the adhesive layer, it is preferable that the weight average molecular weight (Mw) is 15,000 or less, more preferably 10,000 or less, and particularly preferably 5,000 or less. On the other hand, in order to sufficiently suppress the curing shrinkage of the cured layer (adhesive layer), the weight average molecular weight (Mw) of the acrylic oligomer is preferably 500 or more, more preferably 1,000 or more, and particularly preferably 1,500 or more. Specific examples of the (meth)acrylic monomer constituting the acrylic oligomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, S-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,Examples of the methacrylic acid (1 to 20 carbon atoms) alkyl esters include 2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and N-octadecyl (meth)acrylate. Examples of the methacrylic acid (1 to 20 carbon atoms) alkyl esters include cycloalkyl (meth)acrylates (e.g., cyclohexyl (meth)acrylate, cyclopentyl (meth)acrylate, and the like), aralkyl (meth)acrylates (e.g., benzyl (meth)acrylate, and the like), polycyclic (meth)acrylates (e.g., 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, and the like). (meth)acrylate, etc.), hydroxyl group-containing (meth)acrylic acid esters (e.g., hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,3-dihydroxypropylmethyl-butyl (meth)methacrylate, etc.), alkoxy group- or phenoxy group-containing (meth)acrylic acid esters (2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-methoxymethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, etc.), epoxy group-containing (meth)acrylic acid esters (e.g., glycidyl (meth)acrylate, etc.), halogen-containing (meth)acrylic acid esters (e.g., 2,2,2-trifluoroethyl (meth)acrylate, 2,2,Examples of the acrylic oligomer (E) include 2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, etc., and alkylaminoalkyl (meth)acrylates (e.g., dimethylaminoethyl (meth)acrylate, etc.). These (meth)acrylates can be used alone or in combination of two or more. Specific examples of the acrylic oligomer (E) include "ARUFON" manufactured by Toagosei Co., Ltd., "Actflow" manufactured by Soken Chemical & Engineering Co., Ltd., and "JONCRYL" manufactured by BASF Japan Ltd.

[0050] The amount of the acrylic oligomer is preferably 15 parts by weight or less based on 100 parts by weight of the total amount of the monomer components in the adhesive composition. If the content of the acrylic oligomer in the composition is too high, the reaction rate when the composition is irradiated with active energy rays may decrease significantly, resulting in poor curing. On the other hand, in order to sufficiently suppress the curing shrinkage of the adhesive layer, it is preferable that the composition contains 3 parts by weight or more of the acrylic oligomer.

[0051] When a radical polymerizable compound is used, the photopolymerization initiator is appropriately selected depending on the active energy ray. When curing with ultraviolet light or visible light, a photopolymerization initiator that is cleaved by ultraviolet light or visible light is used. Examples of the photopolymerization initiator include benzophenone-based compounds such as benzil, benzophenone, benzoylbenzoic acid, and 3,3'-dimethyl-4-methoxybenzophenone; aromatic ketone compounds such as 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone, α-hydroxy-α,α'-dimethylacetophenone, 2-methyl-2-hydroxypropiophenone, and α-hydroxycyclohexylphenylketone; acetophenone-based compounds such as methoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxyacetophenone, and 2-methyl-1-[4-(methylthio)-phenyl]-2-morpholinopropane-1; benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin methyl ether. These include benzoin ether compounds such as benzoin butyl ether and anisoin methyl ether; aromatic ketal compounds such as benzil dimethyl ketal; aromatic sulfonyl chloride compounds such as 2-naphthalenesulfonyl chloride; photoactive oxime compounds such as 1-phenone-1,1-propanedione-2-(o-ethoxycarbonyl)oxime; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone; camphorquinone; halogenated ketones; acylphosphinoxides; and acylphosphonates.

[0052] The amount of the photopolymerization initiator is 20% by weight or less when the total amount of the active energy ray-curable adhesive composition is taken as 100% by weight. The amount of the photopolymerization initiator is preferably 0.01 to 20% by weight, more preferably 0.05 to 10% by weight, and even more preferably 0.1 to 5% by weight.

[0053] When the curable adhesive for polarizing films of the present invention is used as a visible light curable type containing a radically polymerizable compound as a curable component, it is preferable to use a photopolymerization initiator that is highly sensitive to light of 380 nm or more. Photopolymerization initiators that are highly sensitive to light of 380 nm or more will be described later.

[0054] The photopolymerization initiator may be a compound represented by the following general formula (1):

[0055] [ka] (In the formula, R 1 and R 2 represents -H, -CH2CH3, -iPr or Cl, R 1 and R 2 It is preferable to use a compound represented by general formula (1) alone (which may be the same or different), or to use a compound represented by general formula (1) in combination with a photopolymerization initiator highly sensitive to light of 380 nm or longer, which will be described later. When a compound represented by general formula (1) is used, the adhesiveness is superior to the case where a photopolymerization initiator highly sensitive to light of 380 nm or longer is used alone. Among the compounds represented by general formula (1), R 1 and R 2 Diethylthioxanthone, in which the formula is -CH2CH3, is particularly preferred. The composition ratio of the compound represented by general formula (1) in the adhesive composition is preferably 0.1 to 5 parts by weight, more preferably 0.5 to 4 parts by weight, and even more preferably 0.9 to 3 parts by weight, relative to 100 parts by weight of the total amount of the curable components.

[0056] It is also preferable to add a polymerization initiator aid as necessary. Examples of the polymerization initiator aid include triethylamine, diethylamine, N-methyldiethanolamine, ethanolamine, 4-dimethylaminobenzoic acid, methyl 4-dimethylaminobenzoate, ethyl 4-dimethylaminobenzoate, and isoamyl 4-dimethylaminobenzoate, with ethyl 4-dimethylaminobenzoate being particularly preferable. When using a polymerization initiator aid, the amount added is usually 0 to 5 parts by weight, preferably 0 to 4 parts by weight, and most preferably 0 to 3 parts by weight, based on 100 parts by weight of the total amount of the curable components.

[0057] Also, a known photopolymerization initiator can be used in combination as necessary. Since the transparent protective film having UV absorbing ability does not transmit light of 380 nm or less, it is preferable to use a photopolymerization initiator that is highly sensitive to light of 380 nm or more as the photopolymerization initiator. Specifically, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, etc. can be mentioned.

[0058] In particular, as the photopolymerization initiator, in addition to the photopolymerization initiator of general formula (1), a compound represented by the following general formula (2):

[0059] [ka] (In the formula, R 3 , R 4 and R 5 represents -H, -CH3, -CH2CH3, -iPr or Cl, and R 3 , R 4 and R5 (which may be the same or different) is preferably used. As the compound represented by the general formula (2), 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropan-1-one (trade name: Omnirad 907, manufacturer: IGM Resins), which is also a commercially available product, can be suitably used. In addition, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1 (trade name: Omnirad 369, manufacturer: IGM Resins) and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (trade name: Omnirad 379, manufacturer: IGM Resins) are preferred because of their high sensitivity.

[0060] In the present invention, among the above photopolymerization initiators, it is preferable to use a hydroxyl group-containing photopolymerization initiator. When the active energy ray-curable adhesive composition contains a hydroxyl group-containing photopolymerization initiator as a polymerization initiator, the solubility in the adhesive layer having a high concentration of the A component on the polarizer side is increased, and the curability of the adhesive layer is improved. Examples of photopolymerization initiators having a hydroxyl group include 2-methyl-2-hydroxypropiophenone (trade name "DAROCUR1173", manufactured by BASF), 1-hydroxycyclohexyl phenyl ketone (trade name: Omnirad 184, manufacturer: IGM Resins), 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one (trade name: Omnirad 2959, manufacturer: IGM Resins), 2-hydroxy-1-{4-[4-(2-hydroxy-2-methyl-propionyl)-benzyl]phenyl}-2-methyl-propan-1-one (trade name: Omnirad 127, manufacturer: IGM Resins), etc. In particular, 1-hydroxycyclohexyl phenyl ketone is more preferable because it has excellent solubility in the adhesive layer having a high concentration of component A.

[0061] The cationic polymerizable compound used in the cationic polymerizable adhesive composition is classified into a monofunctional cationic polymerizable compound having one cationic polymerizable functional group in the molecule and a polyfunctional cationic polymerizable compound having two or more cationic polymerizable functional groups in the molecule. Since the liquid viscosity of the monofunctional cationic polymerizable compound is relatively low, the liquid viscosity of the resin composition can be reduced by including it in the resin composition. In addition, the monofunctional cationic polymerizable compound often has a functional group that exhibits various functions, and the cationic polymerizable adhesive composition and / or the cured product of the cationic polymerizable adhesive composition can exhibit various functions by including it in the cationic polymerizable adhesive composition. The polyfunctional cationic polymerizable compound can be three-dimensionally crosslinked in the cured product of the cationic polymerizable adhesive composition, so it is preferable to include it in the cationic polymerizable adhesive composition. The ratio of the monofunctional cationic polymerizable compound to the polyfunctional cationic polymerizable compound is preferably in the range of 10 parts by weight to 1000 parts by weight of the polyfunctional cationic polymerizable compound to 100 parts by weight of the monofunctional cationic polymerizable compound. Examples of the cationic polymerizable functional group include an epoxy group, an oxetanyl group, and a vinyl ether group. Examples of compounds having an epoxy group include aliphatic epoxy compounds, alicyclic epoxy compounds, and aromatic epoxy compounds. It is particularly preferable that the cationically polymerizable adhesive composition of the present invention contains an alicyclic epoxy compound, as these compounds have excellent curability and adhesive properties. Examples of alicyclic epoxy compounds include 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, caprolactone-modified 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, trimethylcaprolactone-modified 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and valerolactone-modified 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate. Specific examples include Celloxide 2021, Celloxide 2021A, Celloxide 2021P, Celloxide 2081, Celloxide 2083, Celloxide 2085 (all manufactured by Daicel Chemical Industries, Ltd.), Cyracure UVR-6105, Cyracure UVR-6107, Cyracure 30, and R-6110 (all manufactured by Dow Chemical Japan, Ltd.).Compounds having an oxetanyl group are preferably contained because they improve the curing property of the cationic polymerizable adhesive composition and reduce the liquid viscosity of the composition. Examples of compounds having an oxetanyl group include 3-ethyl-3-hydroxymethyloxetane, 1,4-bis[(3-ethyl-3-oxetanyl)methoxymethyl]benzene, 3-ethyl-3-(phenoxymethyl)oxetane, di[(3-ethyl-3-oxetanyl)methyl]ether, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, and phenol novolac oxetane, and ARON OXETANE OXT-101, ARON OXETANE OXT-121, ARON OXETANE OXT-211, ARON OXETANE OXT-221, and ARON OXETANE OXT-212 (all manufactured by Toagosei Co., Ltd.) are commercially available. The compound having a vinyl ether group is preferably contained since it has the effect of improving the curing property of the cationic polymerizable adhesive composition and reducing the liquid viscosity of the composition. Examples of the compound having a vinyl ether group include 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, 4-hydroxybutyl vinyl ether, diethylene glycol monovinyl ether, triethylene glycol divinyl ether, cyclohexane dimethanol divinyl ether, cyclohexane dimethanol monovinyl ether, tricyclodecane vinyl ether, cyclohexyl vinyl ether, methoxyethyl vinyl ether, ethoxyethyl vinyl ether, and pentaerythritol tetravinyl ether.

[0062] The cationic polymerizable adhesive composition contains at least one compound selected from the compounds having an epoxy group, the compounds having an oxetanyl group, and the compounds having a vinyl ether group described above as a curable component, and since all of these are cured by cationic polymerization, a photocationic polymerization initiator is blended. This photocationic polymerization initiator generates cationic species or Lewis acid by irradiation with active energy rays such as visible light, ultraviolet light, X-rays, and electron beams, and initiates the polymerization reaction of the epoxy group or the oxetanyl group. As the photocationic polymerization initiator, a photoacid generator described later is preferably used. In addition, when the cationic polymerizable adhesive composition is used as a visible light curable composition, it is preferable to use a photocationic polymerization initiator that is highly sensitive to light of 380 nm or more, but since photocationic polymerization initiators are generally compounds that show maximum absorption in the vicinity of 300 nm or shorter wavelength range, by blending a photosensitizer that shows maximum absorption in light of a longer wavelength range, specifically, a wavelength longer than 380 nm, it is possible to promote the generation of cationic species or acid from the photocationic polymerization initiator by responding to light of this vicinity wavelength. Examples of photosensitizers include anthracene compounds, pyrene compounds, carbonyl compounds, organic sulfur compounds, persulfides, redox compounds, azo and diazo compounds, halogen compounds, photoreducible dyes, etc., and these may be used in combination of two or more. In particular, anthracene compounds are preferred because they have excellent photosensitizing effects, and specific examples include Anthracure UVS-1331 and Anthracure UVS-1221 (manufactured by Kawasaki Chemical Industries, Ltd.). The content of the photosensitizer is preferably 0.1% by weight to 5% by weight, more preferably 0.5% by weight to 3% by weight.

[0063] Each component of the polarizing film according to the present invention will be described below. The polarizing film according to the present invention includes a polarizer and an adhesive layer adjacent to the polarizer or an optical film other than the polarizer.

[0064] <Polarizer> Polyvinyl alcohol or its derivatives are used as the material for the polyvinyl alcohol-based film applied to the polarizer. Examples of polyvinyl alcohol derivatives include polyvinyl formal, polyvinyl acetal, etc., as well as derivatives modified with olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid, their alkyl esters, acrylamide, etc. Polyvinyl alcohols with a degree of polymerization of about 1000 to 10000 and a degree of saponification of about 80 to 100 mol % are generally used.

[0065] The polyvinyl alcohol-based film may contain additives such as a plasticizer. Examples of the plasticizer include polyols and their condensates, such as glycerin, diglycerin, triglycerin, ethylene glycol, propylene glycol, and polyethylene glycol. The amount of the plasticizer used is not particularly limited, but is preferably 20% by weight or less in the polyvinyl alcohol-based film.

[0066] In producing a polarizer, a dyeing step in which the polyvinyl alcohol-based film is dyed with iodine and a stretching step in which the polyvinyl alcohol-based film is stretched in at least one direction are performed. In general, a method is adopted in which the polyvinyl alcohol-based film is subjected to a series of steps including swelling, dyeing, crosslinking, stretching, water washing, and drying steps.

[0067] The swelling step is carried out, for example, by immersing the polyvinyl alcohol film in a swelling bath (water bath). This treatment cleans the surface of the polyvinyl alcohol film from dirt and antiblocking agents, and swells the polyvinyl alcohol film to prevent non-uniformity such as uneven dyeing. Glycerin, potassium iodide, etc. may be appropriately added to the swelling bath. The temperature of the swelling bath is usually about 20 to 60°C, and the immersion time in the swelling bath is usually about 0.1 to 10 minutes.

[0068] The dyeing step is carried out, for example, by immersing the polyvinyl alcohol film in an iodine solution. The iodine solution is usually an aqueous iodine solution, containing iodine and potassium iodide as a dissolving agent. The iodine concentration is usually about 0.01 to 1 wt%, preferably 0.02 to 0.5 wt%. The potassium iodide concentration is usually about 0.01 to 10 wt%, preferably 0.02 to 8 wt%.

[0069] In the iodine dyeing step, the temperature of the iodine solution is usually about 20 to 50° C., preferably 25 to 40° C. The immersion time is usually about 10 to 300 seconds, preferably 20 to 240 seconds. In the iodine dyeing treatment, it is preferable to adjust conditions such as the concentration of the iodine solution, the immersion temperature of the polyvinyl alcohol film in the iodine solution, and the immersion time so that the iodine content and potassium content in the polyvinyl alcohol film are within the above-mentioned ranges.

[0070] The crosslinking step is carried out, for example, by immersing a polyvinyl alcohol film dyed with iodine in a treatment bath containing a crosslinking agent. Any appropriate crosslinking agent is used as the crosslinking agent. Specific examples of the crosslinking agent include boron compounds such as boric acid and borax, glyoxal, and glutaraldehyde. These are used alone or in combination. Water is generally used as a solvent for the crosslinking bath solution, but an appropriate amount of an organic solvent compatible with water may be added. The crosslinking agent is usually used in a ratio of 1 to 10 parts by weight with respect to 100 parts by weight of the solvent. It is desirable that the crosslinking bath solution further contains an auxiliary such as an iodide. The concentration of the auxiliary is preferably 0.05 to 15% by weight, more preferably 0.5 to 8% by weight. The temperature of the crosslinking bath is usually about 20 to 70°C, preferably 40 to 60°C. The immersion time in the crosslinking bath is usually about 1 second to 15 minutes, preferably 5 seconds to 10 minutes.

[0071] The stretching step is a step in which a polyvinyl alcohol-based film is stretched in at least one direction. In general, the polyvinyl alcohol-based film is uniaxially stretched in the conveying direction (longitudinal direction). The stretching method is not particularly limited, and either a wet stretching method or a dry stretching method can be adopted. When the wet stretching method is adopted, the polyvinyl alcohol-based film is stretched to a predetermined ratio in a treatment bath. As a solution for the stretching bath, a solution in which a compound required for various treatments is added to a solvent such as water or an organic solvent (e.g., ethanol) is preferably used. Examples of the dry stretching method include a roll-to-roll stretching method, a heated roll stretching method, and a compression stretching method. In the production of a polarizer, the stretching step may be performed at any stage. Specifically, it may be performed simultaneously with swelling, dyeing, and crosslinking, or may be performed before or after each of these steps. In addition, the stretching may be performed in multiple stages. The cumulative stretching ratio of the polyvinyl alcohol-based film is usually 5 times or more, and preferably about 5 to 7 times.

[0072] In the present invention, the polarizer preferably contains a metal component capable of becoming a divalent metal cation in water, more preferably contains magnesium, calcium, copper or zinc, and particularly preferably contains zinc. When the polarizer contains zinc, the decrease in transmittance and the deterioration in hue of the polarized film after a heating test tend to be suppressed. When the polarizer contains zinc, the content of zinc in the polarizer is preferably 0.002 to 2 wt%, more preferably 0.01 to 1 wt%.

[0073] In the present invention, the polarizer preferably contains sulfate ions. When the polarizer contains sulfate ions, there is a tendency that a decrease in the transmittance of the polarized film after a heating test is suppressed. When the polarizer contains sulfate ions, the content of sulfate ions in the polarizer is preferably 0.02 to 0.45% by weight, more preferably 0.05 to 0.35% by weight, and further preferably 0.1 to 0.25% by weight. The content of sulfate ions in the polarizer is calculated from the sulfur atom content.

[0074] In order to incorporate zinc into the polarizer, it is preferable to carry out a zinc impregnation treatment in the manufacturing process of the polarizer. In order to incorporate sulfate ions into the polarizer, it is preferable to carry out a sulfate ion treatment in the manufacturing process of the polarizer.

[0075] The zinc impregnation treatment is carried out, for example, by immersing the polyvinyl alcohol film in a zinc salt solution. As the zinc salt, an inorganic salt compound such as an aqueous solution of zinc halide such as zinc chloride or zinc iodide, zinc sulfate, or zinc acetate is suitable. In addition, various zinc complex compounds may be used for the zinc impregnation treatment. In addition, it is preferable to use an aqueous solution of potassium ion and iodine ion by potassium iodide or the like as the zinc salt solution, since it is easy to impregnate the zinc ion. The concentration of potassium iodide in the zinc salt solution is about 0.5 to 10% by weight, and more preferably 1 to 8% by weight.

[0076] The sulfate ion treatment is carried out, for example, by immersing the polyvinyl alcohol-based film in an aqueous solution containing a metal sulfate. The metal sulfate is preferably one that is easily separated into sulfate ions and metal ions in the treatment solution and is easily introduced in the form of ions into the polyvinyl alcohol-based film. For example, metals that form metal sulfate include alkali metals such as sodium and potassium; alkaline earth metals such as magnesium and calcium; and transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, and iron.

[0077] In the manufacture of a polarizer, the zinc impregnation treatment and the sulfate ion treatment may be performed at any stage. That is, the zinc impregnation treatment and the sulfate ion treatment may be performed before or after the dyeing step. The zinc impregnation treatment and the sulfate ion treatment may be performed simultaneously. In the present invention, it is preferable to use zinc sulfate as the zinc salt and the metal sulfate salt, and to simultaneously perform the zinc impregnation treatment and the sulfate ion treatment by immersing the polyvinyl alcohol film in a treatment bath containing zinc sulfate. In addition, the zinc salt and the metal sulfate salt may be coexisted in the dyeing solution, and the zinc impregnation treatment and / or the sulfate ion treatment may be performed simultaneously with the dyeing step. The zinc impregnation treatment and the sulfate ion treatment may be performed simultaneously with the stretching.

[0078] In the zinc impregnation treatment and sulfate ion treatment, the zinc content and sulfate ion content in the polarizer are adjusted by adjusting the conditions such as the concentration of the zinc salt solution and the metal sulfate solution, the immersion temperature of the polyvinyl alcohol film in the treatment bath, and the immersion time. In the zinc impregnation treatment and sulfate ion treatment, the temperature of the zinc salt solution and the metal sulfate solution is usually about 15 to 85°C, preferably 25 to 70°C. The immersion time is usually about 1 to 120 seconds, preferably 3 to 90 seconds. The concentration of the zinc salt solution and the metal sulfate solution varies depending on the type of zinc salt and metal sulfate, but is usually about 0.5 to 20% by weight, preferably 1 to 10% by weight, and more preferably 2 to 7% by weight. By setting the zinc salt concentration and the metal sulfate concentration in the above ranges, the zinc content and sulfate ion content in the polarizer can be set within the above preferred ranges.

[0079] The polyvinyl alcohol film (stretched film) that has been subjected to the above-mentioned treatments is subjected to a water washing step and a drying step according to a conventional method.

[0080] The water washing step is usually carried out by immersing the polyvinyl alcohol film in a water washing bath. The water washing bath may be pure water or an aqueous solution of an iodide (e.g., potassium iodide, sodium iodide, etc.). The concentration of the aqueous iodide solution is preferably 0.1 to 10% by weight. An auxiliary such as zinc sulfate or zinc chloride may be added to the aqueous iodide solution.

[0081] The washing temperature is usually in the range of 5 to 50°C, preferably 10 to 45°C, and more preferably 15 to 40°C. The immersion time is usually about 10 to 300 seconds, and preferably 20 to 240 seconds. The washing step may be carried out only once, or may be carried out multiple times as necessary. When the washing step is carried out multiple times, the type and concentration of additives contained in the washing bath used for each treatment are appropriately adjusted.

[0082] The drying process of the polyvinyl alcohol-based film is carried out by any appropriate method (for example, natural drying, air drying, heat drying). The thickness of the polarizer after the drying process is preferably 3 to 20 μm.

[0083] In the present invention, the obtained polarizer may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, and itro treatment, and corona treatment is particularly preferable. By performing corona treatment, reactive functional groups such as carbonyl groups and amino groups are generated on the polarizer surface, and the adhesion to the durability improving layer is improved. In addition, the ashing effect removes foreign matter on the surface and reduces surface unevenness, making it possible to prepare a polarizing film with excellent appearance characteristics.

[0084] <Optical film> In the present invention, examples of the optical film that the polarizing film has include a transparent protective film and a retardation film. In addition to the polarizer, the optical film may also be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, and itro treatment, and corona treatment is particularly preferred.

[0085] As a material for forming the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The transparent protective film may contain one or more types of any appropriate additives. Examples of the additives include ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, coloring inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants. The content of the thermoplastic resin in the transparent protective film is preferably 50 to 100% by weight, more preferably 50 to 99% by weight, even more preferably 60 to 98% by weight, and particularly preferably 70 to 97% by weight. If the content of the thermoplastic resin in the transparent protective film is 50% by weight or less, the inherent properties of the thermoplastic resin, such as high transparency, may not be fully exhibited.

[0086] The material for forming the transparent protective film is preferably one having excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, etc., and in particular, a moisture permeability of 150 g / m 2 / 24h or less is more preferable, and 140g / m 2 / 24h or less is particularly preferred, and 120g / m 2 / 24h or less is even more preferable.

[0087] A functional layer such as a hard coat layer, an anti-reflection layer, an anti-sticking layer, a diffusion layer, an anti-glare layer, etc. may be provided on the surface of the transparent protective film to which the polarizer is not adhered. The functional layer such as the hard coat layer, the anti-reflection layer, the anti-sticking layer, the diffusion layer, the anti-glare layer, etc. may be provided on the transparent protective film itself, or may be provided separately from the transparent protective film.

[0088] The thickness of the transparent protective film can be appropriately determined, but is generally about 1 to 500 μm, preferably 1 to 300 μm, more preferably 5 to 200 μm, further preferably 10 to 200 μm, and more preferably 20 to 80 μm, from the viewpoints of workability such as strength and handleability, thinness, etc.

[0089] As the transparent protective film, a retardation film having a front retardation of 40 nm or more and / or a thickness retardation of 80 nm or more can be used. The front retardation is usually controlled to be in the range of 40 to 200 nm, and the thickness retardation is usually controlled to be in the range of 80 to 300 nm. When a retardation film is used as the transparent protective film, the retardation film also functions as the transparent protective film, so that a thinner film can be achieved.

[0090] Examples of the retardation film include a birefringent film obtained by uniaxially or biaxially stretching a polymer material, an oriented film of a liquid crystal polymer, and an oriented layer of a liquid crystal polymer supported by a film, etc. The thickness of the retardation film is not particularly limited, but is generally about 20 to 150 μm.

[0091] The retardation film may be one represented by the following formulas (1) to (3): 0.70 <Re

[0450] / Re

[0550] <0.97···(1) 1.5×10 -3 <Δn<6×10 -3 (2) 1.13 <NZ<1.50···(3) (wherein Re

[0450] and Re

[0550] are in-plane retardation values ​​of the retardation film measured at 23° C. with light of wavelengths of 450 nm and 550 nm, respectively, Δn is in-plane birefringence, which is nx-ny, when the refractive indices in the slow axis direction and the fast axis direction of the retardation film are nx and ny, respectively, and NZ is the ratio of thickness direction birefringence, nx-nz, to in-plane birefringence, nx-ny, when nz is the refractive index in the thickness direction of the retardation film) may be used.

[0092] The polarizing film according to the present invention can be produced, for example, by the following production method. A method for producing a polarizing film comprising a polarizer and an adhesive layer adjacent to a first optical film other than the polarizer, the adhesive layer being a cured layer of the adhesive composition for polarizing films according to the present invention, the method comprising a first adhesion step of adhering the polarizer and the first optical film via a water-based adhesive layer, and a second adhesion step of adhering the first optical film and a second optical film via the adhesive layer. It is preferable that the polarizer contains a metal component capable of becoming a divalent metal cation in water, particularly zinc. It is also preferable that the adhesive layer is formed from a cured layer of an active energy ray-curable adhesive composition.

[0093] The polarizing film according to the present invention can also be produced, for example, by the following production method. A method for producing a polarizing film including a polarizer and an adhesive layer adjacent to the polarizer, the method comprising a first adhesion step of adhering the polarizer and a first optical film via the adhesive layer. The polarizer preferably contains a metal component capable of becoming a divalent metal cation in water, particularly zinc. In addition, the adhesive layer is preferably formed of a cured layer of an active energy ray-curable adhesive composition.

[0094] In the above-mentioned adhesion step, various adhesive compositions are applied to an adherend such as a polarizer or an optical film, and the adherend such as a polarizer or an optical film is laminated to cure the adhesive composition. The method for applying the adhesive composition is appropriately selected depending on the viscosity of the adhesive composition and the desired thickness, and examples thereof include a reverse coater, a gravure coater (direct, reverse, or offset), a bar reverse coater, a roll coater, a die coater, a bar coater, and a rod coater. The lamination of the adherend such as a polarizer or an optical film can be performed using a roll laminator or the like.

[0095] The adhesive layer is formed from a cured product layer of the adhesive composition for polarizing films according to the present invention. In particular, the adhesive composition is an active energy ray-curable adhesive composition that is electron beam-curable, ultraviolet ray-curable, visible light-curable, or the like, and contains a cation having a coordination site capable of being coordinated with a metal component at two or more sites and a reactive group. capture Preferably, the polarizing film is formed by a cured layer of an active energy ray curable adhesive composition containing an adhesive agent. In the adhesion step, the adhesive composition is cured by irradiating with active energy rays (electron beams, ultraviolet rays, visible light, etc.) to form an adhesive layer. The direction of irradiation of the active energy rays (electron beams, ultraviolet rays, visible light, etc.) can be any appropriate direction. When the polarizing film according to the present invention is produced on a continuous line, the line speed is preferably 5 to 100 m / min, more preferably 10 to 50 m / min, and even more preferably 20 to 30 m / min, depending on the curing time of the adhesive composition. If the line speed is too low, the productivity is poor or the damage to the transparent protective film is too large, and a polarizing film that can withstand a durability test or the like cannot be produced. If the line speed is too high, the curing of the curable resin composition becomes insufficient, and the desired adhesiveness may not be obtained.

[0096] The polarizing film of the present invention can be used as an optical film laminated with other optical layers in practical use. The optical layer is not particularly limited, and one or more optical layers that may be used in the formation of liquid crystal displays, such as a reflector, a semi-transmitting plate, a retardation plate (including a wavelength plate such as 1 / 2 or 1 / 4), or a viewing angle compensation film, can be used. In particular, a reflective polarizing film or semi-transmitting polarizing film obtained by laminating a reflector or semi-transmitting reflector on the polarizing film of the present invention, an elliptical polarizing film or a circular polarizing film obtained by laminating a retardation plate on the polarizing film, a wide viewing angle polarizing film obtained by laminating a viewing angle compensation film on the polarizing film, or a polarizing film obtained by laminating a brightness improvement film on the polarizing film is preferred.

[0097] The optical film obtained by laminating the above-mentioned optical layer on the polarizing film can be formed by sequentially laminating them separately during the manufacturing process of liquid crystal display devices, etc., but the optical film obtained by laminating them in advance has the advantage of being excellent in quality stability and assembly workability, and can improve the manufacturing process of liquid crystal display devices, etc. An appropriate bonding means such as an adhesive layer can be used for lamination. When bonding the above-mentioned polarizing film and other optical films, their optical axes can be arranged at an appropriate angle depending on the desired retardation characteristics, etc.

[0098] The above-mentioned polarizing film or the optical film having at least one layer of polarizing film laminated thereon may be provided with an adhesive layer for adhering to other members such as a liquid crystal cell. The adhesive for forming the adhesive layer is not particularly limited, and may be appropriately selected and used, for example, from those having acrylic polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluorine-based polymers, rubber-based polymers, and the like as a base polymer. In particular, those having excellent optical transparency, such as acrylic adhesives, and adhesive properties such as moderate wettability, cohesion, and adhesiveness, and having excellent weather resistance, heat resistance, and the like, may be preferably used.

[0099] The adhesive layer can be provided on one or both sides of the polarizing film or optical film as a superimposed layer of different compositions or types. When provided on both sides, the adhesive layers on the front and back of the polarizing film or optical film can be different in composition, type, thickness, etc. The thickness of the adhesive layer can be appropriately determined depending on the purpose of use, adhesive strength, etc., and is generally 1 to 100 μm, preferably 5 to 30 μm, and particularly preferably 10 to 20 μm.

[0100] The exposed surface of the adhesive layer is covered with a separator temporarily attached to prevent contamination until it is put into practical use. This prevents contact with the adhesive layer during normal handling. As the separator, apart from the above thickness conditions, any suitable thin material such as a plastic film, a rubber sheet, paper, cloth, nonwoven fabric, net, foam sheet, metal foil, or a laminate thereof, which is coated with a suitable release agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide-based material as necessary, may be used in accordance with conventional methods.

[0101] The polarizing film or optical film of the present invention can be preferably used for forming various devices such as liquid crystal display devices. The formation of a liquid crystal display device can be carried out in accordance with the conventional method. That is, a liquid crystal display device is generally formed by appropriately assembling components such as a liquid crystal cell, a polarizing film or optical film, and an optional lighting system, and incorporating a driving circuit, but in the present invention, there is no particular limitation except that the polarizing film or optical film of the present invention is used, and the method can be carried out in accordance with the conventional method. As for the liquid crystal cell, any type such as TN type, STN type, or π type can be used.

[0102] It is possible to form suitable liquid crystal displays, such as those in which a polarizing film or an optical film is arranged on one or both sides of a liquid crystal cell, or those in which a backlight or a reflector is used in the illumination system. In this case, the polarizing film or optical film according to the present invention can be disposed on one or both sides of a liquid crystal cell. When polarizing films or optical films are provided on both sides, they may be the same or different. Furthermore, when forming a liquid crystal display, suitable components such as a diffusion plate, an anti-glare layer, an anti-reflection film, a protective plate, a prism array, a lens array sheet, a light diffusion plate, a backlight, etc., can be disposed in one or more layers at suitable positions. EXAMPLES

[0103] Examples of the present invention are described below, but the embodiments of the present invention are not limited to these.

[0104] <Manufacture of Polarizer> A polyvinyl alcohol film having an average degree of polymerization of 2700 and a thickness of 45 μm was stretched and conveyed between rolls with different peripheral speed ratios while being dyed. First, the polyvinyl alcohol film was immersed in a water bath at 30° C. for 1 minute to swell and stretched 1.2 times in the conveying direction (first stretching), and then immersed in an aqueous solution (liquid temperature 30° C.) of potassium iodide (0.03 wt %) and iodine (0.3 wt %) for 1 minute to stretch the film 3 times (based on the unstretched film) in the conveying direction while being dyed (second stretching). Next, this stretched film was stretched 6 times (based on the unstretched film) in the conveying direction while being immersed in an aqueous solution (bath liquid) of boric acid (4 wt %), potassium iodide (5 wt %) and zinc sulfate (3.5 wt %) for 30 seconds (third stretching). This stretched film was dried to obtain polarizer 1. The thickness of polarizer 1 after drying was 18 μm.

[0105] <Active energy rays> Visible light (gallium-filled metal halide lamp) as active energy rays Irradiation device: Light HAMMER10 manufactured by Fusion UV Systems, Inc. Bulb: V bulb Peak illuminance: 1600mW / cm 2 , cumulative dose 1000 / mJ / cm 2 The illuminance of visible light was measured using a Sola-Check system manufactured by Solatell.

[0106] <Panel lighting test> A MAXWIN vehicle-mounted on-dash monitor (TKH703) was disassembled to take out a liquid crystal panel. The polarizing film attached to the viewing side of this liquid crystal panel was peeled off, and instead, the polarizing films according to the respective examples and comparative examples manufactured were cut to the same size as the polarizing film peeled off from the liquid crystal panel, and were attached to the peeled off polarizing film via an adhesive layer (thickness 20 μm) so that the transmission axis was the same as that of the peeled off polarizing film, thereby obtaining a liquid crystal panel.

[0107] The liquid crystal panel obtained above was placed in an environment of 65°C and 95% humidity for 1000 hours, and then left in a normal temperature and humidity environment for 24 hours. After that, the liquid crystal panel was remounted in the disassembled monitor case, and a black image was displayed and visually confirmed. As a result, if only a black screen was displayed, it was marked as ◯, and if a white haze-like display defect occurred in part of the screen, it was marked as ×.

[0108] <Third optical film> The third optical film (retardation film) used in the polarizing film configuration below was produced by the following production method.

[0109] In an autoclave equipped with a stirrer, a cooling tube, a nitrogen inlet tube and a thermometer, 48 parts by weight of hydroxypropyl methylcellulose (manufactured by Shin-Etsu Chemical, trade name Metolose 60SH-50), 15601 parts by weight of distilled water, 8161 parts by weight of diisopropyl fumarate, 240 parts by weight of 3-ethyl-3-oxetanylmethyl acrylate and 45 parts by weight of t-butyl peroxypivalate as a polymerization initiator were placed, and after nitrogen bubbling for 1 hour, the mixture was stirred and held at 49°C for 24 hours to carry out radical suspension polymerization. The mixture was then cooled to room temperature, and the suspension containing the produced polymer particles was centrifuged. The obtained polymer was washed twice with distilled water and twice with methanol, and then dried under reduced pressure.

[0110] The obtained fumarate ester resin (polymer with negative birefringence) was dissolved in a toluene-methyl ethyl ketone mixed solution (toluene / methyl ethyl ketone 50% / 50% by weight) to prepare a 20% solution. Furthermore, 5 parts by weight of tributyl trimellitate as a plasticizer was added to 100 parts by weight of the fumarate ester resin to prepare a dope.

[0111] The support film used was a biaxially stretched polyester (polyethylene terephthalate / isophthalate copolymer) film (thickness 75 μm, width 1350 mm). The tensile modulus (MD) of the support at 140° C. was 800 MPa.

[0112] The roll of the support film was set in the unwinding section of the film-forming device, and the support film was unwound and transported downstream while being heat-treated in a heating furnace. The temperature of the heat treatment was adjusted by changing the atmospheric temperature in the heating furnace. The heating time was adjusted by changing the transport speed of the support. The dope prepared in Synthesis Example A was applied to the support after the heat treatment so that the film thickness after drying would be 6.3 μm, and dried at 140° C. The coating film after drying was wound up as a laminate together with the support.

[0113] The laminate was set in the unwinding section of the stretching device, and while the laminate was unwound and conveyed downstream, it was subjected to free-end uniaxial stretching in a stretching furnace at a temperature of 140°C. The support was peeled off from the laminate after stretching to obtain a retardation film with a thickness of 6 μm. The stretching ratio was adjusted so that the in-plane retardation of the retardation film after peeling off the support was 35 nm.

[0114] Example 1 As the adhesive, an aqueous solution containing an acetoacetyl group-containing polyvinyl alcohol resin (average polymerization degree 1200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylol melamine in a weight ratio of 3:1 was used. Using this adhesive, a second optical film (a triacetyl cellulose film with a hard coat layer (manufactured by Fujifilm Corporation, product name "TG40UL", film thickness 40 μm)) was laminated to one surface (viewing side surface) of the polarizer 1, and a first optical film (a cycloolefin film with retardation (manufactured by Zeon Corporation, product name "ZT12", film thickness 17 μm)) was laminated to the other surface (image display cell side surface) of the polarizer 1 using a roll laminator (the thickness of each aqueous adhesive layer was 0.1 μm), and then the laminated film was heated and dried in an oven to produce a laminated film in which the optical films were laminated on both sides of the polarizer.

[0115] Next, the adhesive composition adjusted to the blending amount shown in Table 1 was applied to the retardation-added cycloolefin film side of the laminated film obtained above using an MCD coater (manufactured by Fuji Machine Co., Ltd.) (cell shape: honeycomb, gravure roll line count: 1000 rolls / inch, rotation speed 140% / to line speed) to a thickness of 1 μm, and the laminate was laminated to the third optical film (film thickness 6 μm) using a roll machine. Thereafter, the adhesive composition was cured by irradiating the above-mentioned visible light from the third optical film side using an active energy ray irradiation device, and then dried with hot air at 70° C. for 3 minutes to obtain a polarizing film. The thickness of the adhesive layer after drying was 1 μm. The lamination line speed was 25 m / min.

[0116] A sample for evaluating humidity durability test was prepared by bonding the polarizing film (500 μm×500 μm) according to Example 1 produced to one side of a 0.7 mm thick non-alkali glass sheet via an adhesive layer (thickness 20 μm). The sample was placed in an environment of 65° C.-95% humidity, and then exposed for 500 hours or 1000 hours to conduct a humidity durability test. For the sample for evaluating humidity durability test after the humidity durability test, a cross-Nicol polarizing film was bonded to the other side of the non-alkali glass sheet to which the polarizing film according to Example 1 was bonded, via an adhesive layer (thickness 20 μm), so that the transmission axes of the polarizing films were perpendicular to each other, and then the sample was placed on a backlight (with the polarizing film according to Example 1 on top), and the polarizing film according to Example 1 was visually observed, and the number of bright spots due to foreign matter was counted within a range of 500 μm×500 μm.

[0117] Examples 2 to 11 and Comparative Examples 1 to 10 The number of bright spots caused by foreign matter was counted in the same manner as in Example 1, except that the formulation of the adhesive composition and the thickness of the adhesive layer after drying were changed to those shown in Table 1.

[0118] Details of each component listed in Table 1 are as follows. "FA1DDM" (unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone); product name "Placcel FA1DDM", manufactured by Daicel Corporation "ACMO" (Acryloylmorpholine); Trade name "ACMO", manufactured by KJ Chemicals "9EG-A" (PEG400 diacrylate); product name "Light Acrylate 9EG-A", manufactured by Kyoeisha Chemical Co., Ltd. "UP-1190" (acrylic oligomer obtained by polymerizing (meth)acrylic monomers); product name "Alphon UP-1190", manufactured by Toagosei Co., Ltd. "AAEM" (2-acetoacetoxyethyl methacrylate) (used in combination with ethylenediamine to form a cation scavenger); product name "AAEM", manufactured by Mitsubishi Chemical Corporation "Ethylenediamine" (ethylenediamine) (used in combination with AAEM to form a cation scavenger); product name "Ethylenediamine", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. "DMAPAA" (Dimethylaminopropylacrylamide) (cation scavenger); Trade name "DMAPAA", manufactured by KJ Chemicals "DMAEA" (N,N-dimethylaminoethyl acrylate) (cation scavenger); product name "DMAEA", manufactured by KJ Chemicals "X-12-967C" (3-trimethoxysilylpropylsuccinic anhydride) (cation scavenger); product name "X-12-967C", manufactured by Shin-Etsu Chemical Co., Ltd. "Acrylic acid" (acrylic acid) (additive); product name "acrylic acid", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. "HOA-MS" (2-acryloyloxyethyl succinic acid) (additive); product name "HOA-MS", manufactured by Kyoeisha Chemical Co., Ltd. "HOA-HH" (2-acryloyloxyethylhexahydrophthalic acid) (additive); product name "HOA-HH", manufactured by Kyoeisha Chemical Co., Ltd. "M-5300" (ω-carboxy-polycaprolactone (n≒2) monoacrylate) (additive); product name "Aronix M-5300", manufactured by Toagosei Co., Ltd. "DMAA" (Dimethylacrylamide) (additive); Trade name "DMAA", manufactured by KJ Chemicals "QM-HA05" (quaternary ammonium salt type ionic liquid with ethylenically unsaturated bonds) (additive); product name "QM-HA05", manufactured by KJ Chemicals "QM-KA05" (quaternary ammonium salt type ionic liquid with ethylenically unsaturated bonds) (additive); product name "QM-KA05", manufactured by KJ Chemicals "Omn.907" (2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropan-1-one) (additive); trade name "Omnirad 907", manufactured by IGM Resins "DETX-S" (2,4-dimethylthioxanthone) (additive); product name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.

[0119] [Table 1]

[0120] From the results in Table 1, it can be seen that the polarizing films having adhesive layers formed using the polarizing film adhesive compositions of Examples 1 to 11 as raw materials have a small number of bright spots and have excellent appearance characteristics even after 1000 hours in an environment of 65°C and 95% relative humidity. On the other hand, the polarizing films having adhesive layers formed using the adhesive compositions of Comparative Examples 2 to 10 as raw materials, which contain an additive that does not have a coordination site that can coordinate to a metal component at two or more sites, have a large number of bright spots and have poor appearance characteristics even after 500 hours in an environment of 65°C and 95% relative humidity. [Explanation of symbols]

[0121] 10 Polarizing film 1 Polarizer 2. Water-based adhesives 3,4,6 Optical Film 5 Adhesive layer 7 Adhesive layer

Claims

1. A polarizing film comprising a polarizer and an adhesive layer adjacent to the polarizer or an optical film other than the polarizer, the adhesive layer is a cured layer of an adhesive composition for polarizing films, and contains oxalic acid; the adhesive composition for polarizing films contains a compound having a radically polymerizable functional group of a carbon-carbon double bond, and a cation scavenger having a coordination site capable of being coordinated to a metal component at two or more denatures and a reactive group, a polarizing film, wherein the reactive group of the cation scavenger is at least one type of reactive group selected from the group consisting of a vinyl group, a (meth)acrylic group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a mercapto group, and an alkoxy group.

2. The polarizing film according to claim 1 , wherein the coordination site of the cation scavenger has at least two nitrogen atoms.

3. The polarizing film according to claim 1 , wherein the coordination site of the cation scavenger has at least two oxygen atoms.

4. The polarizing film according to claim 1 , wherein the coordination site of the cation scavenger has at least one nitrogen atom and at least one oxygen atom.

5. 2. The polarizing film according to claim 1, wherein the cation scavenger is at least one selected from the group consisting of aminoalkylacrylamides, aminoalkylacrylates, and reaction products of acetoacetyl- or acetoacetoxyl-containing compounds with primary amine compounds.

6. 6. The polarizing film according to claim 1, wherein the content of the cation scavenger is 0.5 to 15% by weight when the total amount of the adhesive composition for polarizing films is taken as 100% by weight.

7. 7. The polarizing film according to claim 1, wherein the polarizer contains a metal component capable of becoming a divalent metal cation in water.

8. 8. The polarizing film according to claim 1, wherein the metal component is zinc.

9. The polarizing film according to any one of claims 1 to 8, comprising a polarizer, an optical film laminated on at least one surface of the polarizer via an aqueous adhesive layer, and the adhesive layer on a surface of the optical film opposite to the aqueous adhesive layer.

10. 10. An optical film comprising at least one polarizing film according to claim 1 laminated thereon.

11. 11. An image display device comprising the polarizing film according to claim 1 and / or the optical film according to claim 10.

Citation Information

Patent Citations

  • Manufacture of polarizing element

    JP1979016575A

  • Method for manufacturing polarizing plate and liquid crystal display device

    JP2001296427A

  • Polarizer, polarizing plate and liquid crystal display device

    JP2003029042A

  • Polarizer, its manufacturing method, polarizing plate, optical film and image display apparatus

    JP2006047978A

  • Active energy ray-curable resin composition, adhesive layer, polarizing plate, optical film, and image display device

    JP2012052000A